2021
DOI: 10.1111/geb.13385
|View full text |Cite
|
Sign up to set email alerts
|

Local community assembly processes shape β‐diversity of soil phoD‐harbouring communities in the Northern Hemisphere steppes

Abstract: Aim The contemporary coexistence theory suggests that species pool, environmental filtering, dispersal assembly processes, ecological drift and biotic interactions collectively determine the β‐diversity of communities. However, we know little about the biogeographical patterns of the β‐diversity of microbial communities harbouring the alkaline phosphatase phoD gene (phoD communities, hereafter) and whether these mechanisms are all‐important in shaping phoD communities’ β‐diversity in natural steppe ecosystems.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 71 publications
2
19
1
Order By: Relevance
“…The homogenized resource was found to decrease variation in beta diversity of soil bacterial communities (Jiao et al, 2018; Leibold & McPeek, 2006). Additionally, we found that the homogeneous enrichment of bacteria in deep soils contributed a large fraction to bacterial community assembly (Figure 4a), which will ultimately result in lower beta diversity (Stegen et al, 2015; Xu et al, 2021). These explanations were supported by the strong dependence of beta diversity in deep layer on soil moisture variation (Table S2) and by the significant correlation between Bray–Curtis dissimilarity and potential biotic interactions based on co‐occurrence network observed in this study (Figure S11b) and previous studies (Wang et al, 2021; Xu et al, 2021).…”
Section: Discussionmentioning
confidence: 93%
“…The homogenized resource was found to decrease variation in beta diversity of soil bacterial communities (Jiao et al, 2018; Leibold & McPeek, 2006). Additionally, we found that the homogeneous enrichment of bacteria in deep soils contributed a large fraction to bacterial community assembly (Figure 4a), which will ultimately result in lower beta diversity (Stegen et al, 2015; Xu et al, 2021). These explanations were supported by the strong dependence of beta diversity in deep layer on soil moisture variation (Table S2) and by the significant correlation between Bray–Curtis dissimilarity and potential biotic interactions based on co‐occurrence network observed in this study (Figure S11b) and previous studies (Wang et al, 2021; Xu et al, 2021).…”
Section: Discussionmentioning
confidence: 93%
“…In each climatic zone, we also calculated the difference of climatic factors (both temperature and humidity) and soil properties (the rst three axes of PCA of soil properties) between paired plots (hereafter climatic distance and soil distance). Comparisons between climatic distance, soil distance and Bray-Curtis community similarity across the three study sites were done using Wilcoxon test [37]. The relationship between β-diversity (Bray-Curtis similarity) and geographic (elevation, latitude and longitude) or elevational distance was analyzed using loess regression.…”
Section: Discussionmentioning
confidence: 99%
“…Presumably higher levels of functional redundancy would increase neutrality and make these functionally redundant taxa more vulnerable to drift. The high proportion of ecological drift in forest ecosystems is a special case when compared with other ecosystems such as grassland or steppe ecosystems [37], which indicates that the high levels of competition among species as well as tight nutrient cycling dynamics in a forest environment seem to be important considerations for soil bacterial and fungal functions and understanding these environmental modulators could be a starting point for future work.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed information about each site (soil type, plant community, etc.) was described in a previous study (Xu et al, 2021).…”
Section: Site Descriptionsmentioning
confidence: 99%